Development of Integrated Electronic Module with Instructional Videos - Santri Chintia Purba (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
This research was conducted to develop a teaching material product for teaching Mathematics. The product developed is an electronic module containing instructional videos aimed at addressing common issues in online learning. The research method used was Research and Development (R&D). The R&D stages included analyzing field needs, designing the concept of the developed product, designing the product itself, and validating the product with three experts: Content Validator, Media Validator, and Language validator. Based on the questionnaire validation from the experts on the e-module development, the findings are as follows: Content validation scored 73.5 out of 75 in total, or 4.9 out of 5 on a scale of 5. The score interval obtained was 98%, indicating that the content validity criteria are highly valid. Language validation aspect indicated that the language used is highly valid, scoring 50 out of 50 in total, or 5 out of 5 on a scale of 5, meeting the 100% validity criteria. Media validation scored 65.33 out of 75, or 4.35 out of 5 on a scale of 5. The score interval obtained was 87%, indicating that the media validity criteria are very valid.